2014
DOI: 10.1037/a0037829
|View full text |Cite
|
Sign up to set email alerts
|

A Bruner-Potter effect in audition? Spoken word recognition in adult aging.

Abstract: Bruner and Potter (1964) demonstrated the surprising finding that incrementally increasing the clarity of images until they were correctly recognized (ascending presentation) was less effective for recognition than presenting images in a single presentation at that same clarity level. This has been attributed to interference from incorrect perceptual hypotheses formed on the initial presentations under ascending conditions. We demonstrate an analogous effect for spoken word recognition in older adults, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
(75 reference statements)
3
14
0
Order By: Relevance
“…As might be expected from age and inhibition arguments, the older adults in the study showed a larger interference effect from ascending presentations than the young adults. Germaine to our present question, a follow-up regression analysis revealed that participants’ reading spans, taken as a measure of working memory capacity ( Daneman and Carpenter, 1980 ; McCabe et al, 2010 ), contributed significantly to the size of the interference effect (see Lash and Wingfield, 2014 , for full details). The reading span test, which we discuss in a subsequent section, was used rather than a listening span version (e.g., Wingfield et al, 1988 ) to avoid a potential confound with hearing acuity.…”
Section: Age and Inhibition In Word Recognition: The Role Of Working mentioning
confidence: 78%
See 4 more Smart Citations
“…As might be expected from age and inhibition arguments, the older adults in the study showed a larger interference effect from ascending presentations than the young adults. Germaine to our present question, a follow-up regression analysis revealed that participants’ reading spans, taken as a measure of working memory capacity ( Daneman and Carpenter, 1980 ; McCabe et al, 2010 ), contributed significantly to the size of the interference effect (see Lash and Wingfield, 2014 , for full details). The reading span test, which we discuss in a subsequent section, was used rather than a listening span version (e.g., Wingfield et al, 1988 ) to avoid a potential confound with hearing acuity.…”
Section: Age and Inhibition In Word Recognition: The Role Of Working mentioning
confidence: 78%
“…This effect of working memory span on the effectiveness of inhibition can be illustrated most clearly in Figure 2 in which we have taken data from Lash and Wingfield (2014) and have plotted the percentage of correct identifications for the same gate size when words were presented in the fixed versus the ascending presentation conditions separated by participants’ working memory span. A participant was considered to have a high working memory span (left panel) if they scored greater than one standard deviation above the mean for their age cohort determined by McCabe et al (2010) , or a low span if they did not (right panel).…”
Section: Age and Inhibition In Word Recognition: The Role Of Working mentioning
confidence: 97%
See 3 more Smart Citations